A control strategy for stand-alone wound rotor induction machine - Forchetti, Daniel Gustavo (2007)
A control strategy to regulate the frequency and voltage of a stand-alone wound rotor induction machine is presented. This strategy allows the machine to work as a generator in stand-alone systems (without grid connection) with variable rotor speed. A stator flux-oriented control is proposed using the rotor voltages as actuation variables. Two cascade control loops are used to regulate the stator flux and the rotor currents. A closed loop observer is designed to estimate the machine flux which is necessary to implement these control loops. The proposed control strategy is validated through simulations with satisfactory results.